Semiconductor power devices physics, characteristics, reliability - Lutz, Josef; SpringerLink (Online service). (Heidelberg New York Springer, 2011)
Semiconductor power devices are the heart of power electronics. They determine the performance of power converters and allow topologies with high efficiency. Semiconductor properties, pn-junctions and the physical phenomena for understanding power devices are discussed in depth. Working principles of state-of-the-art power diodes, thyristors, MOSFETs and IGBTs are explained in detail, as well as key aspects of semiconductor device production technology. In practice, not only the semiconductor, but also the thermal and mechanical properties of packaging and interconnection technologies are essential to predict device behavior in circuits. Wear and aging mechanisms are identified and reliability analyses principles are developed. Unique information on destructive mechanisms, including typical failure pictures, allows assessment of the ruggedness of power devices. Also parasitic effects, such as device induced electromagnetic interference problems, are addressed. The book concludes with modern power electronic system integration techniques and trends.
Power Semiconductor Devices ? Key Components for Efficient Electrical Energy Conversion Systems -- Semiconductor Properties -- pn - Junctions -- Short introduction to power device technology -- pin-Diodes -- Schottky Diodes -- Bipolar Transistors -- Thyristors -- MOS Transistors -- IGBTs -- Packaging and Reliability of Power Devices -- Destructive Mechanisms in Power Devices -- Power Device Induced Oscillations and Electromagnetic Disturbances -- Power Electronic Systems -- Appendix -- Index.
Electronic reproduction.
Keywords: Power semiconductors; Electronic books